Коралина: [повесть] / Нил Гейман; иллюстратор Крис Ридделл; [перевод с английского Е. Кононенко] - Гейман Нил (АСТ, 2017)
Экземпляры: ф. 6 (20230309) / Инвентарный номер: 65309 / Цена: 50.00 / Авт.знак: Г 29 / ГРНТИ: 17.82.93 / ББК: 84(4Вел)-44